2022
DOI: 10.1002/jgh3.12805
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for liver‐related mortality of patients with hepatitis C virus after sustained virologic response to direct‐acting antiviral agents

Abstract: Background and Aim The aim of this study was to identify the factors associated with liver‐related and non‐liver‐related mortality of patients with hepatitis C virus (HCV) after sustained virologic response (SVR) to direct‐acting antiviral agents (DAAs). Methods We conducted a retrospective, single‐center cohort study of HCV patients cured by DAAs. Results A total of 330 patients with SVR to DAAs were eligible. The median follow‐up period was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Moreover, patients with a history of HCC who experienced HCC recurrence after SVR had higher mortality rates than those without recurrence (5,14). Recent studies have revealed that liver cancer accounts for 51.9%-90% of liver-related deaths in DAA-treated patients after SVR (5,15,16). These findings collectively highlight the significant impact of HCC occurrence on patient outcomes and underscore the importance of HCC surveillance despite achieving viral clearance after DAAs treatment.…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, patients with a history of HCC who experienced HCC recurrence after SVR had higher mortality rates than those without recurrence (5,14). Recent studies have revealed that liver cancer accounts for 51.9%-90% of liver-related deaths in DAA-treated patients after SVR (5,15,16). These findings collectively highlight the significant impact of HCC occurrence on patient outcomes and underscore the importance of HCC surveillance despite achieving viral clearance after DAAs treatment.…”
Section: Introductionmentioning
confidence: 91%
“…Regarding liver steatosis, HCV is known to contribute to lipogenesis, lipoprotein synthesis, and fatty acid oxidation, so its eradication can improve steatotic liver disease [67]. Other factors that have been described as associated with HCC development include age, male sex, genotype 1 infection, history of HCC, and pre-treatment alpha-fetoprotein levels [58,68]. The eradication of HCV infection has also been shown to be associated with a significant reduction in the risk of cardiovascular and all-cause mortality [59,61,69].…”
Section: Prognostic Benefit Of Svrmentioning
confidence: 99%